Pathological diagnosis of peritoneal loose body: a case report (Journal of Pathology of Nepal, 2013)
Peritoneal loose bodies are usually incidental findings at laparotomy. Their sizes range from that of a pea to giant loose bodies. We report a case of giant loose peritoneal body measuring 5x 4 cm found incidentally in a 67 year old man. Mobile pelvic masses are extremely rare findings. They are usually located in the pelvic cavity due to the fact that they gravitate to the most dependent part of the pelvic cavity. Usually these peritoneal loose bodies are left untreated until complications arise. DOI: http://dx.doi.org/10.3126/jpn.v3i6.9005   Journal of Pathology of Nepal (2013) Vol. 3, 512-514